2021
DOI: 10.1371/journal.pntd.0009660
|View full text |Cite
|
Sign up to set email alerts
|

Assessing early child development and its association with stunting and schistosome infections in rural Zimbabwean children using the Griffiths Scales of Child Development

Abstract: There is a paucity of reference early childhood development (ECD) data at community level in rural Africa. Our objective was to conduct a comprehensive assessment of ECD in rural Zimbabwe and determine the impact of stunting and schistosome infections on ECD. Using the Griffiths Scales of Child Development, we conducted a cross sectional assessment of Eye and Hand Coordination (EHC), Personal-Social-Emotional (PSE), Language and Communication (LC), Foundations of Learning (FL) and Gross Motor (GM) domains and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 32 publications
0
6
0
1
Order By: Relevance
“…This problem was also clearly highlighted in a recent update of a Cochrane systematic review [ 89 ], in which the authors report they were unable to perform planned subgroup analyses due to too few studies. A very recent study [ 23 ] looking at early childhood development, stunting and schistosomiasis in Zimbabwe has already begun to address this evidence gap.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This problem was also clearly highlighted in a recent update of a Cochrane systematic review [ 89 ], in which the authors report they were unable to perform planned subgroup analyses due to too few studies. A very recent study [ 23 ] looking at early childhood development, stunting and schistosomiasis in Zimbabwe has already begun to address this evidence gap.…”
Section: Discussionmentioning
confidence: 99%
“…Children are especially vulnerable to infection due to their hygiene and play habits [ 22 ]. A recent study [ 23 ] showed that preschool-age children (PSAC) with schistosomiasis had significantly poorer early childhood development scores, but that these improved to the same levels as un-infected children with anthelmintic treatment. Along with children, pregnant and breastfeeding women have also been suspected as potential high-risk groups for helminth infections [ 16 ], due to hormonal changes and possible immunosuppression [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nutritional status was scored using the WHO child growth standards from the WHO Anthro software, version 3.0.1( http://www.who.int/childgrowth/en/ ) as described in a previous study ( 33 ). Briefly, measurements of height, weight and the mid upper arm circumference (MUAC) were taken from PSAC using a stadiometer (Gima ® ), electronic scale (Gima ® ) and MUAC tape (AnthroFlex ® ) respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Regarding outcome, the global child development was assessed by the GSCD (third edition) [4,15] a widely used [17][18][19] specialistic tool exploring five key evolutionary areas: the "Foundations of Learning" subscale (scale A), the "Language and Communication" subscale (scale B), the "Eye and Hand Coordination" subscale (scale C), the "Personal-Social-Emotional" subscale (scale D) and the "Gross Motor" subscale (scale E). Subscale scores and a total score, the "General Development score" (GDS) were calculated.…”
Section: Variablesmentioning
confidence: 99%